DETECTION OF EARNINGS MANIPULATION; EVIDENCES FROM SRI LANKA - Wijesinghe, M.R.P.; Perera, W.T.N.M.; Yashodha, K.A.D.H. (University of Jaffna, 2021)
Stream of literature on earnings management highlighted managers' opportunistic behavior to manipulate financial information with the view of extracting numerous unethical benefits. The purpose of this study is to investigate whether earnings manipulation exists in Sri Lanka as fabricating earnings which adversely triggers to the economy as a whole. We utilized Beneish model in our study as this model is a widely accepted, successful and important fraud sensitive indicator in detecting earnings manipulation under specific accruals method. As the sample, we considered twenty listed firms from Colombo Stock Exchange (CSE) for the period of 2013 to 2017 on quarterly basis. Days Receivable Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI), Sales General and Admin Expense Index (SGAI), Leverage Index (LVGI) and Total Accruals to Total Asset Index (TATA) were used to calculate the M-Score of the model which determines the susceptible companies where earnings manipulation could exist. Results, reveals that earnings manipulation exists in the entities listed on CSE at different degrees based on financial structure of such companies operating in different sectors. Our findings facilitate regulatory authorities to enhance effectiveness of standard-setting and monitoring to eliminate dodges where earnings could be manipulated. In addition, the study contributes to the knowledge base of academics and policymakers to make effective economic decisions.
Keywords: Beneish Model; Earnings Management; Fraud Detection; M-Score; Sri Lanka